A SIRT1-centered circuitry regulates breast cancer stemness and metastasis. Issue 49 (6th December 2018) - Shi, Lei; Tang, Xiaolong; Qian, Minxian; Liu, Zuojun; Meng, Fanbiao; Fu, Li; Wang, Zimei; Zhu, Wei-Guo; Huang, Jian-Dong; Zhou, Zhongjun; Liu, Baohua
Abstract Cancer stem cell (CSC)-dictated intratumor heterogeneity accounts for the majority of drug-resistance and distant metastases of breast cancers. Here, we identify a SIRT1-PRRX1-KLF4-ALDH1 circuitry, which couples CSCs, chemo-resistance, metastasis and aging. Pro-longevity protein SIRT1 deacetylates and stabilizes the epithelial-to-mesenchymal-transition (EMT) inducer PRRX1, which inhibits the transcription of core stemness factor KLF4. Loss ofSIRT1 destabilizes PRRX1, disinhibits KLF4, and activates the transcription ofALDH1, which induces and functionally marks CSCs, resulting in chemo-resistance and metastatic relapse. Clinically, the level of PRRX1 is positively linked to SIRT1, whereas KLF4 is reversely correlated. Importantly, KLF4 inhibitor Kenpaullone sensitizes breast cancer cells and xenograft tumors to Paclitaxel and improves therapeutic effects. Our findings delineate a SIRT1-centered circuitry that regulates CSC origination, and targeting this pathway might be a promising therapeutic strategy.